Analisis Penerapan Kearifan Lokal Masyarakat dalam Konservasi Erosi Tepi Sungai Desa Pulau Terap, Kabupaten Kampar, Provinsi Riau - Hadisty, Cindy Dian; Chandra, Deded (Lembaga Yasin AlSys, 2025)
This study analyzes the application of local community wisdom in riverbank erosion conservation in Desa Pulau Terap, Kecamatan Kuok, Kabupaten Kampar, Riau Province. The research aims to identify and analyze: (1) forms of local wisdom in riverbank erosion conservation, (2) factors inhibiting its implementation, and (3) efforts to mitigate erosion threats based on local wisdom. A qualitative approach was used, with informants selected through purposive sampling. Data analysis was conducted through the stages of data collection, reduction, presentation, and conclusion drawing. The findings indicate that local wisdom has been applied through two methods: vegetative techniques and traditional civil engineering using floating fish cages (keramba apung) along the river. Inhibiting factors include waste disposal into the river, land-use changes around the riverbanks, and unregulated sand and stone mining activities. Community and village government efforts to reduce erosion threats include issuing warnings, enforcing sanctions, and conducting outreach programs by village officials and niniok mamak (traditional leaders), both verbally and in writing, to raise public awareness of the importance of preserving the river environment. These findings confirm that integrating local wisdom into environmental conservation can serve as an effective strategy for sustainable natural resource management.